Between nihilism and politics : the hermeneutics of Gianni Vattimo - Benso, Silvia; Schroeder, Brian, 1959- (SUNY series in contemporary Italian philosophy., 2010)
This is the first collection of essays in English that deals directly with the philosophy of Gianni Vattimo from a purely critical perspective, further establishing his rightful place in contemporary European philosophy. Vattimo, who first came to prominence as the translator of Gadamer's Truth and Method into Italian, is now considered to be more than a philosopher and prolific author. As a former member of the European Parliament (1999-2004), he is also a public intellectual. This book takes up his call to advance the crucial active and affirmative engagement with thinking and society. More than just interpretations of Vattimo's thinking, these essays are expressions of the new impetus given to hermeneutic philosophy by "weak thought," the term he coined for how we think now in the wake of Nietzsche, Heidegger, and Gadamer. The development of Vattimo's thinking is reflected in the organization of the volume, divided into three main parts: Hermeneutics and Nihilism, Metaphysics